Centro Integral de Rehabilitación para Personas con Discapacidades en Neiva – Huila (2020)
Disability is a condition of human beings, caused by different genetic-hereditary factors, general illness, work accidents, and accidents in homes, having as its main characteristic the deprivation of a factor as important as body mobility, sight , eyes, voice and speech, generating limitations to participate in economic, social and cultural life at the regional, national and world levels. Over time this condition has been stigmatized, to such an extent that the connotation of disabled has also been considered from the recrimination of the individual and society. The above has created barriers to access for this population to the labor market, education, recreation, public facilities, sports, among other activities. Hence the fundamental intention of this project, which is to design an architectural project which promotes the inclusion of the population with disabilities in the department of Huila, through spaces for the promotion of sports, recreation, culture, training for productive work, and improving their health through rehabilitation